Prevalencia y evolución de la apendicitis aguda en pacientes del Hospital Belén de Trujillo - Aguirre, Elizabeth (2018)
Acute appendicitis is the most common surgical emergency around the world, and that appendectomy is one of the most common surgical procedures. The peak incidence is between the second and the third decade of life. Although the majority of patients with acute appendicitis has uncomplicated illness, complicated appendicitis is relatively common with an incidence similar for all age groups.  We have found that more and more elderly people are being diagnosed with appendicitis, although in a later stage of disease. Some authors have suggested that the appendicitis in the elderly is commonly associated with a delay in the diagnosis and a high rate of complications. We also found that within the Department La Libertad, the patients from nearby provinces attend is with more incidence geographically, although we also found very remote places patients who often are the complicated. The purpose of the study is intended to determine the prevalence and evolution of the acute appendicitis in the La Libertad Department, with data taken from the archive of the Hospital Belen of Trujillo, during the five-year period 2011-2015, in order to have a glimpse of the reality of this disease so prevalent, but in our region.